Perbandingan pelapisan Chitosan dan Beeswax terhadap kualitas Jeruk Keprok (Citrus Reticulata L.) aksesi K32 dan K10 di BSIP Jestro Kota Batu Jawa Timur - Tamamiya, Nilta Ukkida (Maliki Interdisciplinary Journal, 2023)
One of the horticultural product commodities in Indonesia which has a high market demand is Tangerines. The Ministry of Agriculture stated that the production of tangerines in 2014 could reach 92% of the total production of all oranges. In line with this, handling during the harvesting and storage processes must be considered so that the quality of the fruit is maintained. One way to maintain the quality of citrus fruits is to apply a coating of chitosan and beeswax on the surface of the peel. The purpose of this coating is so that the quality of the fruit can be better and have a longer shelf life. This study used Factorial RAK using 1.5% chitosan and 6% beeswax treatment. The results showed that tangerines (accessions K32 and K10) covered with beeswax had a lower proportion of reduction in weight loss, diameter and height than those covered with chitosan. Thus, the best coating material is 6% beeswax. During storage, tangerine fruit (accessions K32 and K10) experienced a trend of changing color to become lighter (degreening at room temperature). Tangerine fruit stored with chitosan coating has a more glossy skin, while the beeswax-coated fruit looks duller. One of the things that became a problem during storage was the presence of fungus (green mold) which grew more on the K10 accession tangerines which caused rot.